Controle de doenças foliares causadas por fungos no milho por meio da aplicação de óleos essenciais - Silva, Janaina Costa e (Universidade Federal do Tocantins, 2020)
Research with essential oil of noni as an alternative control method for plants are still rare diseases. Thus, the objective of this study was to evaluate the efficiency of this essential oil in the control Exserohilum turcicum, causal agent of Exserohilum spot in maize. In health test 400 seeds were incubated at Blotter Test method. To test transferability were removed injured fragments of leaves of plantlets placed on PDA culture medium and taken to the incubator. To check the pathogenicity was performed Postulate Koch. In phytotoxicity test was used noni oil different concentrations applied in maize seedlings. E. turcicum Conidia were subjected to different noni oil concentrations. In the preventive and curative essential oil was applied noni before and after inoculation, conidia, respectively. The results revealed the presence of fungi of the genus Aspergillus, Penicillium, Rhizopus, Fusarium and Exserohilum in corn seeds. It was confirmed the pathogenicity of E. turcicum and also the transmission of this fungus of seed for corn seedlings. Concentrations from 1% noni oil were phytotoxic corn seedlings. Inhibition of spore germination was proportional to the increase of concentrations. Preventive application of essential oil noni was more effective in controlling Mancha Exserohilum than curative application.